AL-ISYKALIYAAT AL-LUGHOWIYAH FI ALFAADZI-L-QUR’ANI-L-KAREEM - Zakinah, Zunah; Mufidah, Nur Rohmatul (Institut PTIQ Jakarta, 2020)
This study aims to explain some of the secrets and wisdom behind language problems in the word Al-Qur'an with semantics. To obtain scientific data, the researchers used the literature method with primary data sources in the form of literature and language interpreter books such as the interpretation of Al-Zamakhsyari or Al-Alusi. Secondary data is data that supports primary data. The data of this research were obtained by using descriptive method, namely collecting and analyzing related data sources which were followed up with the analytical method by analyzing these data, examined through a semantic approach, namely the approach of language meaning. The results in this discussion the researcher discusses four problematic aspects in the Qur'an, namely the discontinuity between ma'thuf and ma'thuf alaihi, between ifrod, tasniyah, and jama ', between na'at and man'ut, and ta'nis. al-mudzakkar and tadzkir al-muannas, these problems essentially do not violate the rules of Arabic language or grammar, and the scholars of the Qur'an have explained in detail the wisdom of the existence of the text structure, and precisely because of that lies the characteristics of I'jaz Al -The Qur'an that cannot be understood only from the grammatical aspect.